Neighbourhood effects on station-level transit use: Evidence from the Taipei metro. (June 2021) - Andersson, David Emanuel; Shyr, Oliver F.; Yang, Jimmy
Abstract: While large high-density metropolitan areas with extensive transit networks experience greater use of rail transit than elsewhere, less is known about the neighbourhood effects that affect station use. This study applies the 5D model to analyse neighbourhood effects within 600 m of transit stations in the Taipei metropolitan area. The area is separated into three concentric zones, with separate functions for each zone. While population density, destination attractiveness, and distance to intermodal connections are important in all three zones, design features depend on their location vis-à-vis the centre. Intersection density is important in the downtown core, while bike share facilities affect station use in the intermediate ring. A geographically weighted regression (GWR) reveal that most 5D variables exhibit spatial serial dependence. The key GWR result is that population density has the greatest effect on station use in peripheral residential neighbourhoods.